Byssal re‐attachment behavior in the winged pearl oyster Pteria penguin in response to low salinity levels - Hebert Ely Vasquez; Zheng Xing; Xin Zhan; Zhifeng Gu; Aimin Wang (Journal of the World Aquaculture Society, 2021)
Abstract The effect of low salinity levels on byssal re‐attachment behavior in Pteria penguin juveniles was observed in the laboratory. Juvenile pearl oysters were submerged in seawater blended to 8.0, 12.0, 16.0, 20.0, 24.0, 28.0, and 32.0 salinity levels for a period of 48 hr. The sub‐lethal salinity level was greater than 20.0 psu. Although salinity levels of 20.0 and 24.0 psu did not affect the oyster survival, the observed byssogenesis activity was significantly reduced and locomotion activity was delayed. Description of the effects of low salinity levels on the byssal re‐attachment behavior of P. penguin juveniles provides a foundation for the design of more complex experiments and approaches to further the exploration and development of improved pearl production techniques.